Genetic dissection of flour whiteness through genome-wide association analysis in common wheat (Triticum aestivum L.) - Jinna Hou; Hui Deng; Fuxin Xu; Shenghui Geng; Congcong Liu; Wenxu Li; Xia Shi; Zhengqing Wu; Zhensheng Lei; Zhengfu Zhou (Current Plant Biology)
The color of flour products has an important influence on consumer acceptance. Flour color is largely determined and measured by the index of flour whiteness (FW) in China. In this study, an association population comprising 207 wheat (Triticum aestivum) accessions originating from seven countries was used for dissection of FW-related genetic loci through genome-wide association analysis. Six quantitative trait loci (QTLs) significantly associated with FW were identified, accounting for 7.87–16.53 % of the total phenotypic variation. Four KASP markers were developed from single-nucleotide polymorphisms associated with the QTLs QFW.HAAS-1AS, QFW.HAAS-1BL, QFW.HAAS-5AL, and QFW.HAAS-7AL. The phytoene synthase-encoding gene TraesCS7A03G1357000 (TaPsyA1) was identified as a candidate gene for QFW.HAAS-7AL. Two allelic variants of TaPsyA1 (designated PsyA1-a and PsyA1-b) were differentiated on the basis of a 37 bp insertion/deletion polymorphism in the second intron. PsyA1-b included the 37 bp insertion, which led to a translational frameshift in the gene and was associated with higher FW. The PsyA1-a allele lacked the 37 bp insertion and was classified into two haplotypes according to the number of repeated ‘TC’ units in a simple sequence repeat in the promoter region. Of the two PsyA1-a haplotypes, the Type 1 haplotype conferred higher FW, flour brightness, and flour redness, and lower yellow pigment content and flour yellowness. The KASP markers and PsyA1 polymorphic markers developed in the present study are suitable for use in molecular marker-assisted selection for improvement of wheat FW.